The origins of G12P[6] rotavirus strains detected in Lebanon. (17th March 2021) - Reslan, Lina; Mishra, Nischay; Finianos, Marc; Zakka, Kimberley; Azakir, Amanda; Guo, Cheng; Thakka, Riddhi; Dbaibo, Ghassan; Lipkin, W. Ian; Zaraket, Hassan
Abstract : The G12 rotaviruses are an increasingly important cause of severe diarrhoea in infants and young children worldwide. Seven human G12P[6] rotavirus strains were detected in stool samples from children hospitalized with gastroenteritis in Lebanon during a 2011–2013 surveillance study. Complete genomes of these strains were sequenced using VirCapSeq-VERT, a capture-based high-throughput viral-sequencing method, and further characterized based on phylogenetic analyses with global RVA and vaccine strains. Based on the complete genomic analysis, all Lebanese G12 strains were found to have Wa-like genetic backbone G12-P[6]-I1-R1-C1-M1-A1-N1-T1-E1-H1. Phylogenetically, these strains fell into two clusters where one of them might have emerged from Southeast Asian strains and the second one seems to have a mixed backbone between North American and Southeast Asian strains. Further analysis of these strains revealed high antigenic variability compared to available vaccine strains. To our knowledge, this is the first report on the complete genome-based characterization of G12P[6] emerging in Lebanon. Additional studies will provide important insights into the evolutionary dynamics of G12 rotaviruses spreading in Asia.